Identification Of Low Molecular Weight Metabolites That Can Predict Low Dose Aspirin Induced Gastric Toxicity And Resistance In Rats And Stable Coronary Artery Disease Patients Using Nmr-Based Pharmacometabonomics - Abubakar, Sha’aban (2019)
Low Dose Aspirin (LDA) is the cornerstone of secondary prevention in coronary artery disease (CAD). Despite its established efficacy, it suffers a major setback of causing gastrointestinal toxicity. In addition, some patients still experience atherothrombotic events while on aspirin secondary prophylaxis, a term known as aspirin resistance. The reasons why some people experience its serious gastric toxicity while others do not is still poorly understood. Likewise, the reason why some patients are adequately protected from a secondary event while others experience another event is yet to be adequately understood. The aim of this project was to evaluate the use of pharmacometabonomics, in finding novel metabolites that can predict aspirin-induced gastric toxicity and aspirin resistance in rats. It also aimed at validating such metabolites in CAD patients. The study involved 2 phases, namely the discovery phase in rats and the validation phase in humans. Pre-dose models were developed using H-NMR spectroscopic data from the biofluids of Sprague Dawley (SD) rats and the respective class identities of the rats. The data were initially subjected to multivariate statistical analysis including principal component analysis and orthogonal-partial least square discriminant analysis. The class identities were either gastric toxic versus non-gastric toxic or aspirin resistant versus aspirin sensitive for the gastric toxicity and aspirin resistance studies respectively.